Metabolic dysfunctions in polycystic ovary syndrome (Journal of Medicine, 2024)
Polycystic Ovary Syndrome (PCOS) is a condition that involves various metabolic dysfunctions such as insulin resistance (IR), hyperandrogenemia, obesity, dyslipidemia, and steroid hormone irregularities. Although the exact cause of PCOS is still unknown, it is known to cause several hormonal disturbances, including hyperandrogenemia, IR, and hyperinsulinemia. Insulin appears to disrupt all components of the hypothalamic-pituitary-ovarian (HPO) axis, and ovarian tissue insulin resistance results in impaired metabolic signaling. This causes hyperandrogenemia, which is one of the primary causes of the symptoms of PCOS. Androgens may also lead to IR by modifying muscle tissue composition and functionality and increasing levels of free fatty acids, perpetuating the IR-hyperinsulinemia-hyperandrogenemia cycle. Obesity exacerbates hormonal imbalances, and in combination with dyslipidemia, amplifies cardiovascular and cerebrovascular risks. This review discusses the complex risk factors of PCOS, including genetic, epigenetic, and environmental factors. It also discusses the interconnected etiologies of metabolic dysfunctions of PCOS, its effective management, and metabolic consequences such as cardiovascular and cerebrovascular diseases.J MEDICINE 2024; 25: 68-77